Vitamin A in Stargardt disease—an evidence-based update. (3rd September 2018) - Federspiel, Cecilie Aalund; Bertelsen, Mette; Kessel, Line
ABSTRACT: Background : High intake of vitamin A is suspected to be a risk factor for the progression of Stargardt disease (STGD1) and many health authorities recommend Stargardt patients not to use oral vitamin A supplements outside that provided naturally in the food. The present study provides the first systematic review of the current level of evidence regarding the role of supplementary vitamin A in STGD1. Materials and methods : We conducted a systematic scientific literature search in the Pubmed database on studies reporting on the effect of oral vitamin A or serum retinol on visual function. Results : In animal studies neither high nor low serum retinol in an Abca4 knockout mouse model of Stargardt showed any effect on electroretinography (ERG). In humans, significantly better visual function was reported in a cross-sectional study of patients with a low dietary intake of vitamin A, whereas a prospective study did not find any correlation between vitamin A supplementation and visual acuity. A newly introduced vitamin A substitute (C20-D(3)-vitamin A) has shown promising effects on ERG in a Stargardt mouse model. Conclusions : There are few studies on the effect of vitamin A in STGD1. The scarcity and inconclusiveness of evidence available impel further research efforts to reach a more confident conclusion. Currently, recommendations to avoid vitamin A dietary supplementation rely mainly on a theoretical background. Animal studies on vitamin A substitute as a possible therapeutic approach in preventing or slowing vision loss in STGD1 seems promising but further clinical trials are needed to verify the results.